From pollution to progress: a decomposition analysis of decoupling performance for industrial pollution in China - Zheng, Huan; Zhang, Hongchen; Qian, Yuan; Chen, Zan; Zhao, Lin; Wang, Sulian (Frontiers in Environmental Science, 2025)
China’s industrial sector drives economic growth but exacerbates energy-environment conflicts, posing challenges to sustainable development. Despite China’s nationwide emission reduction efforts, the persistence of subnational disparities in mitigation performance and the determinants underlying these variations remain understudied. Employing the Tapio decoupling method, this study quantifies the spatiotemporal decoupling of three key industrial pollutants (sulfur dioxide, nitrogen oxide, and smoke/dust) from industrial economic growth, followed by the Logarithmic Mean Divisia Index (LMDI) decomposition method to identify their driving factors. Based on panel data from 2000 to 2020 across 30 Chinese provinces, the results reveal that strong decoupling prevailed during the study period, temporally aligned with national energy and emission policy adjustments. Furthermore, provincial-level analysis reveals that economically less developed regions lag in decoupling performance. Finally, decomposition analysis demonstrates that population growth and economic expansion hinder decoupling, while reductions in industrial emission coefficients, energy intensity, and cleaner energy structures promote it. These findings, constrained by production-based emissions data, highlight that early industrial upgrading, not just post-growth regulation, is critical for synergistic economy-environment development.